Assessment Of Knowledge, Attitude And Practices Of Healthcare Professionals Towards Pharmacovigilance Activites In Lahore, Pakistan: A Mixed Methods Approach - Hussain, Rabia (2020)
Adverse Drug Reactions (ADRs) are associated with a high rate of morbidity and mortality worldwide. To overcome the ADR related problems, many countries around the world have established national pharmacovigilance (PV) systems. Most of the PV systems rely on Spontaneous ADR reporting (SADR) by healthcare professionals (HCPs) such as physicians, pharmacists, and nurses. This thesis aims to explore the knowledge, attitude and practices of HCPs, by using mixed methodology and an intervention study regarding ADR reporting in Pakistan and perceived barriers and facilitators to improve pharmacovigilance activities.